EFEITOS DO ÓLEO ESSENCIAL DE LAVANDULA ANGUSTIFOLIA NA REDUÇÃO DO ESCORE DE DEPRESSÃO EM MULHERES OBESAS - Nunes, Larissa Santos (2021)
Introduction: The aromatherapy is a natural non-invasive practise that uses essential oils which promotes wellness and diseases treatment improving. Among the essential oils types, Lavandula angustifolia stands out. Lavandula angustifolia has been widely researched by a several authors and has shown calming effects, reducing chronic and acute pain, as well as reducing anxiety/and/or depression scores. Thus, the objective was to evaluate the effect of Lavandula angustifolia essencial oil in association with the aid of heated stones massage on the depression score in obese women. Metodology: A double-blind, randomized clinical trial was performed. The sample consisted of 38 obese women between 20 to 60 years old. The study data were collected in two phases, the first in April 2019 and the second between September do October of the same year, in the Physiotherapy practical teaching laboratory at the Universidade Franciscana in the city of Santa Maria/RS. In the both phases of the studying, the participants were randomised and divided into two groups. Intervention (G1) – received the massage with heated stones aid with 3% OeLA solved sweet almond oil, Placebo (G2) – received the massage with heated stones aid with sweet almond oil. The intervention was constituted by 8 massage sessions, which lasted 35 minutes with an average interval of 72 hours between them. To assess the presence and intensity of the depressive symptoms, was used the Beck Depression Inventory (BDI) before and after intervention, a survey questionnaire with sociodemographic variables, and anthropometric measurements of body weight and height were measured. Results: The massage with the aid of heated stones and LaEO significantly reduced the depression score in the intervention group (G1) (p=0,003) when comparing pre and post values. However when the comparison is made between the two groups (G1) and (G2), the results are not statisticaly significant (p=0,067). Conclusion: This research evinced that the LaEO in association with heated stone massages decreased the depression scores in obese women. This fact, together with the ease of access to the oil and the absence of any adverse effects reported, suggest that LaEO may represent na auxiliary treatment for against depression in obese women. Finally, more studies are suggested with larger sample of both sexes, using different LaEO concentrations and nutricional monitoring.